Collected Poems - Perse, Saint-John (Book collections on Project MUSE., 2014)
The Collected Poems of the Nobel laureate and poet-statesman are here reissued with the posthumous Song for an Equinox, to form a complete edition of his poetic oeuvre, including also his I960 Nobel speech On Poetry"" and his 1965 essay on Dante. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable page